2018
DOI: 10.1111/1365-2435.13242
|View full text |Cite
|
Sign up to set email alerts
|

Animal‐mediated organic matter transformation: Aquatic insects as a source of microbially bioavailable organic nutrients and energy

Abstract: Animal communities are essential drivers of energy and elemental flow in ecosystems. However, few studies have investigated the functional role of animals as sources of dissolved organic matter (DOM) and the subsequent utilization of that DOM by the microbial community. In a small forested headwater stream, we tested the effects of taxonomy, feeding traits, and body size on the quality and quantity of dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) excreted by aquatic insects. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 58 publications
3
22
1
Order By: Relevance
“…Importantly, aggregate nutrient and DOM excretion rates were driven by body size and taxonomy of individuals within assemblages, highlighting the fundamental control of animal metabolism and stoichiometry on biogeochemical cycling (Vanni & McIntyre, 2016). Additionally, we revealed functional diversity of organic matter and nutrient cycling traits within a functional group (filter‐feeders) that scale to the ecosystem, expanding previous work demonstrating such diversity among functional groups (Hopper et al., 2018; Parr et al., 2019). Overall, we provided evidence that biogeochemical hotspots associated with animal biomass and stoichiometric traits may constitute a large source of microbially available dissolved nutrient and energy subsidies.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Importantly, aggregate nutrient and DOM excretion rates were driven by body size and taxonomy of individuals within assemblages, highlighting the fundamental control of animal metabolism and stoichiometry on biogeochemical cycling (Vanni & McIntyre, 2016). Additionally, we revealed functional diversity of organic matter and nutrient cycling traits within a functional group (filter‐feeders) that scale to the ecosystem, expanding previous work demonstrating such diversity among functional groups (Hopper et al., 2018; Parr et al., 2019). Overall, we provided evidence that biogeochemical hotspots associated with animal biomass and stoichiometric traits may constitute a large source of microbially available dissolved nutrient and energy subsidies.…”
Section: Discussionsupporting
confidence: 74%
“…Body size mediated excretion rates of DOM, N, and P. Although variable, increasing DOM excretion rates with increasing body size parallels those for inorganic nutrients excreted by mussels in our study and previous studies of animal‐mediated nutrient cycling (Vanni & McIntyre, 2016). This result highlights the influence of metabolism, driven by body size, on animal‐mediated DOM transformation (Meyer & O'Hop, 1983; Parr et al., 2019). Body size is the strongest predictor of nutrient excretion rates across vertebrate and invertebrate taxa because allometric metabolic scaling leads to higher per capita, but lower mass‐specific excretion rates in large animals (Vanni & McIntyre, 2016).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…First, biodeposited caddisfly faecal pellets likely leach dissolved organic matter (DOM) into the hyporheic zone. Previous studies have demonstrated that bioavailable carbon can control biogeochemical activity in the streambed and the leeching of DOM from animal faecal pellets makes up a substantial proportion of available DOM for heterotrophic organisms (Jumars, Penry, Baross, Perry, & Frost, 1989; Parr, Capps, Inamdar, & Metcalf, 2019; Reeder et al, 2018; Urban‐Rich, 1999). Second, caddisfly nets directly increase the surface area available for heterotrophic biofilm colonization in the interstitia.…”
Section: Discussionmentioning
confidence: 99%